2020
DOI: 10.7759/cureus.9178
|View full text |Cite
|
Sign up to set email alerts
|

Role of Morphological and Hemodynamic Factors in Predicting Intracranial Aneurysm Rupture: A Review

Abstract: Intracranial aneurysms (IAs) carry the risk of rupture, which will lead to subarachnoid hemorrhage, which has a high mortality and morbidity risk. However, the treatment of IA's carries mortality and morbidity risks too. There are well-known risk factors for the rupture of IAs like age, size, and site. However, choosing patients with unruptured IAs for treatment is still a big challenge. This review article aimed to find out the relationship between morphological and hemodynamic characters of IAs with their ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…While previous studies using CFD simulation reported that inflow angle may positively correlate with WSS and the inflow velocity 2,8 . Actually, results from CFD were under the condition of an idealized model with other parameters controlled including aneurysm size, location, aspect ratio, and hypertension, which all could contribute to aneurysm hemodynamics change 9,10 . Interestingly, in this study, it was also found that aneurysm size showed a negative trend toward inflow velocity and WSS, which was supported by another CFD study 25 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…While previous studies using CFD simulation reported that inflow angle may positively correlate with WSS and the inflow velocity 2,8 . Actually, results from CFD were under the condition of an idealized model with other parameters controlled including aneurysm size, location, aspect ratio, and hypertension, which all could contribute to aneurysm hemodynamics change 9,10 . Interestingly, in this study, it was also found that aneurysm size showed a negative trend toward inflow velocity and WSS, which was supported by another CFD study 25 .…”
Section: Discussionsupporting
confidence: 80%
“…It has been reported that, in side‐wall aneurysms, blood flow hemodynamic environment of the aneurysm can change with the increased inflow angle 2,8 . Moreover, hemodynamics, influenced and mediated by morphological parameters, have been proposed to be a driven factor of inflammation processes in the aneurysmal wall, which has been suggested as the key mediator of aneurysm initiation and progression 9–13 . Thus, in side‐wall aneurysms, inflow angle may impact hemodynamics and further affect inflammation processes in the aneurysmal wall, since inflammation processes like inflammatory cell infiltration could be initiated by abnormal hemodynamics 13,14 …”
mentioning
confidence: 99%
“…However, on the basis of significant brain atrophy and vascular degeneration in our elderly cohort, we consider that a larger bleeding volume and more diffuse distribution of SAH could be noted after the rupture of an aneurysm with larger size. Aneurysms with a wide neck, however, are characterized by slower blood flow, less turbulence formation and lower shear stress, which has been widely reported as a factor related to a lower risk of rupture, compare to those with a narrow neck (31). With more stable pressure and hemodynamics across the lesion, rupture of a wide-necked aneurysm might be less likely to cause widespread bleeding in the subarachnoid space (32).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, significantly lower OSI was only observed for the high-WSS group. The role of OSI in aneurysm forming and rupture remains controversial ( 27 ).…”
Section: Discussionmentioning
confidence: 99%